O PAPEL DA EDUCAÇÃO INFANTIL NO DESENVOLVIMENTO DAS INTELIGÊNCIAS MÚLTIPLAS RELACIONADAS AOS CAMPOS DE EXPERIÊNCIA DA BASE NACIONAL COMUM CURRICULAR - Bassotto, Bárbara de Almeida (2020)
Kindergarten, the first stage of basic education, is of utmost importance for the development of Multiple Intelligences (MI), which is a distinct way of processing information that can be activated in a cultural setting to solve problems or create products that are valued in a culture. In the present context of a globalized, multicultural society connected to the instantaneous information there is the emergence of a new human behavior, which is complex, creative and fluid, and school has been increasingly challenged in its formative, reflective and critical function. In this understanding, complexity allows methodologies of permanent collective reconstruction that are conceived in planning and understood as a learning process in all dimensions of pedagogical and scientific action. From the context presented in this research, the main objective is to investigate the importance of early childhood education in the development of MI related to the fields of experience of the Common National Curricular Base (CNCB) for children at kindergarten of the City Education Network, in Santa Maria, RS. The research is qualitative and a case study type, with methodological procedures based on the observation of a pedagogical practice and on the narrative analysis of the class teacher. Thus, we obtained data from classroom contexts that provided indications for considering the relationship of the development of Multiple Intelligences to the Fields of Experience proposed by the BNCC. It can be inferred from the development of research and observation, that early childhood education is one of the stages of basic education that offers the possibility of better developing the MI, because the BNCC enables the work through the fields of experience. In summary, the school action of Basic Education made possible through the Fields of Experience provides individual elaboration and abstract thinking that does not restrict children only to school learning, but to a series of experiences related to daily life.